Correlates of Cervical Cancer Screening among Vietnamese American Women. (13th September 2012) - Ma, Grace X.; Fang, Carolyn Y.; Feng, Ziding; Tan, Yin; Gao, Wanzhen; Ge, Shaokui; Nguyen, Cuc
Abstract : Objective . Vietnamese American women are at the greatest risk for cervical cancer but have the lowest cervical cancer screening rates. This study was to determine whether demographic and acculturation, healthcare access, and knowledge and beliefs are associated with a prior history of cervical cancer screening among Vietnamese women. Methods . Vietnamese women (n = 1450 ) from 30 Vietnamese community-based organizations located in Pennsylvania and New Jersey participated in the study and completed baseline assessments. Logistic regression analyses were performed. Results . Overall levels of knowledge about cervical cancer screening and human papillomavirus (HPV) are low. Factors in knowledge, attitude, and beliefs domains were significantly associated with Pap test behavior. In multivariate analyses, physician recommendation for screening and having health insurance were positively associated with prior screening. Conclusion . Understanding the factors that are associated with cervical cancer screening will inform the development of culturally appropriate intervention strategies that would potentially lead to increasing cervical cancer screening rates among Vietnamese women.